The use of Geoelectrical Methods for Delineation of Lead-Zinc Mineralization: A Case Study of Eziama Village, Abia State, South- East, Nigeria - , O. J. Airen; , D. A. Babaiwa (Archives of Current Research International, 2021)
2D Electrical Resistivity (ER) and Instantaneous Potential (IP) geophysical techniques were used at Eziama village in Abia state of Nigeria to investigate possible Pb-Zn mineralization. The dipole-dipole electrode configuration was employed for data acquisition and Earth Imager software was used for inversion of the acquired data. The analysis of the result of the study showed the presence of the Pb-Zn ore along traverses 1, 2 and 3 while traverses 4 and 5 appear barren. Along traverse 1, the mineralized zone falls within the fractured basement and is characterized by low resistivity (about 316 – 5623 ohm-m) and high chargeability (33.2 – 128 ns) at lateral distance of 73 – 103 m. On traverse two, the ore body was identified at lateral distance of about -18 to 53 m as delineated on the IP structure with resistivity and chargeability of the anomalous zone ranging from 4.6 – 677 ohm-m and 41.8 – 142 ns respectively at depth of about 21.4 m while on traverse three, two ore bodies labeled a, a’ and b, b’ on the ER and IP cross-sections were delineated at lateral distance of about -130 to -93 m and 78 to 98 m respectively with depth to the top of the suspected ore bodies ranging from about 7.1 m for body ‘a’ and about 14.3 m for ‘a’. Traverses four and five however showed no prospect for Pb-Zn mineralization. The result of this investigation has once again demonstrated the usefulness of combined electrical resistivity and induced polarization techniques in solid mineral exploration.